Non Linear Simulation And Analysis Of A Neoprene Rubber Gasket - Wahyono Sapto Widodo (President University, 2022)
The paper presents nonlinear simulation and analysis of the neoprene rubber gasket in the bolted joint connection. FE software ANSYS with nonlinear capability is used to make FE model and to simulate the hyperelastic neoprene rubber gasket. The aims of the research are to find the contact stress and the deformation of the neoprene rubber gasket. The maximum contact stress between the gasket and flanges is evaluated to predict the maximum internal fluid pressure that can be withstood by the neoprene gasket, while the maximum deformation is used to evaluate the geometry or dimension of the gasket. The result shows that the maximum contact stress in the gasket is 0.218 MPa at 20 N.m of bolt torsion, while the maximum deformation is 7.1942 mm in the Y axis which occured at 20 N.m of bolt torsion. The maximum deformation of the gasket does not interfere with the bolt position hence this condition is accepted for real application. Based on the current theory and the simulation results, the maximum internal fluid pressure that can be resisted should be less than 0.218 MPa otherwise the fluid will leak across the gasket.